Cross‐reacting recombinant porcine FVIII inhibitors in patients with acquired haemophilia A. Issue 6 (30th September 2020) - Bowyer, Annette; Shepherd, Fiona; Platton, Sean; Guy, Susan; Kitchen, Steve; Maclean, Rhona
Abstract: Introduction: Acquired haemophilia A (AHA) is a rare bleeding disorder caused by the development of autoantibodies to endogenous human factor VIII (hFVIII). If treatment of bleeding is required, one option is recombinant porcine FVIII (rpFVIII). Cross‐reactivity between factor VIII inhibitors and rpFVIII has previously been described. Aim: The aim of this study was to retrospectively assess the incidence of cross‐reacting anti‐porcine inhibitors in patients diagnosed with AHA in two UK centres. Methods: The plasma of fifty‐one patients diagnosed with AHA via reduced FVIII:C and positive FVIII inhibitor titre as detected with a Nijmegen‐Bethesda assay (NBA) was also tested by a porcine Bethesda assay (PBA). The NBA was modified by replacement of human FVIII with rpFVIII in the PBA, with determination of residual FVIII by one‐stage clotting assay. Results: The median FVIII inhibitor titre by NBA was 22.8 BU/mL (range: 0.8‐1000 BU/mL). 37% of samples exhibited linear, type 1 kinetics in the NBA. Negative PBA was observed in 26 patients, and 25 were positive (median PBA: 3.5 BU/mL; range: 0.8‐120 BU/mL). Type 1 kinetics were observed in 40% of PBA‐positive patients. At NBA tires of greater than 100 BU/mL, the positive predictive value for the presence of porcine cross‐reactivity was 100%. At NBA below 5 BU/mL, the negative predictive value for the presence of porcine cross‐reactivity was 71%. Conclusion: Cross‐reactivity between FVIII inhibitors and rpFVIII was observed in 49% of patients. The presence of inhibitors to rpFVIII may influence the treatment choice for patients with acquired haemophilia A.